Blue-emitting fluorophosphate phosphor to enhance color rendition of near-ultraviolet LED white light - Nguyen Van Dung; Nguyen Le Thai; Thuc Minh Bui; Huu Phuc Dang (Indonesian Journal of Electrical Engineering and Computer Science, 2024)
This work presents a novel blue phosphor, Na2MgPO4F: Eu2+ (NMPF: Eu) for violet 405-nm light-emitting diode (LED) devices. The compound is synthesized via a simple one-step sintering process using readily available precursors. Notably, NMPF: Eu exhibits highly efficient and thermally stable blue emission when excited by violet light. The NMPF: Eu is applied to produce a white LED device driven by a 405 nm LED chip and Y3Al5O12: Ce3+ (YAG: Ce) yellow phosphor. The impacts of NMPF: Eu phosphors are investigated by varying their particle size while maintaining consistent doping concentrations. Impressively, the LED prototype displays a substantial reduction in blue light emission while generating white light with enhanced color rendering and luminous properties. These results highlight the suitability and potential of NMPF: Eu as a promising phosphor for widening violet LED applications, especially in generating white light perceptible to the human eyes.